The process of adjustment over time following stroke: A longitudinal qualitative study. Issue 9 (21st October 2019) - Theadom, Alice; Rutherford, Sandy; Kent, Bruce; McPherson, Kathryn; ,
ABSTRACT: Understanding how people adjust following stroke is essential to optimise recovery and ensure services are responsive to people's needs. This study aimed to explore people's experiences over the first three years post-stroke and identify what helped or hindered recovery. As part of a longitudinal, qualitative descriptive study, 55 people and 27 significant others purposefully selected from a population-based stroke incidence study were interviewed 6, 12, 24 and 36 months post-stroke. Interviews were audio taped and transcribed verbatim. Participants described an ongoing process of shock, disruption, and fear, making sense of what happened, needing to fit in with what's offered, finding what works for them and evolving a new normal, whilst managing the ups and downs of life . This process needed to be re-negotiated over time, as people experienced changes in their recovery, comorbidities and/or wider circumstances. The adjustment process continued over the three years post-stroke, even for those who perceived that they were recovering well. Rehabilitation services need to support patients to make sense of their stroke, navigate the health system, address individual concerns and priorities and to know what, when and how much to challenge themselves. Rehabilitation plans need to be revised as circumstances change to facilitate adjustment following a stroke.